liver disease. Clinical case of liver cirrhosis against the background of non-steroidal anti-inflammatory drugs - E. Yu. Plotnikova; E. N. Baranova; O. A. Vorosova; M. S. Кaryagina; K. A. Krasnov (Лечащий Врач)
Drug lesions of the liver account for about 10% of all side reactions of the macrobody associated with the use of pharmacological preparations. The article describes the main mechanisms of drug injury to the liver. Diagnosis of drug liver damage is often difficult and requires the physician not only to carefully collect the history of the patient with the developed disease, but also to have a good orientation in its clinical and morphological manifestations. A clinical case of drug cirrhosis of the liver is given, when the patient for many years overused various non-steroidal anti-inflammatory drugs, which led to a fatal outcome.